2016
DOI: 10.1371/journal.pgen.1005952
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Social Insect Polyphenism Facilitated by the Sex Differentiation Cascade

Abstract: The major transition to eusociality required the evolution of a switch to canalize development into either a reproductive or a helper, the nature of which is currently unknown. Following predictions from the ‘theory of facilitated variation’, we identify sex differentiation pathways as promising candidates because of their pre-adaptation to regulating development of complex phenotypes. We show that conserved core genes, including the juvenile hormone-sensitive master sex differentiation gene doublesex (dsx) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 61 publications
4
54
0
Order By: Relevance
“…temperature and nutrition) or genetic (e.g. sex chromosomes and genetic caste determination) factors leading to development of alternative phenotypic states (Brian, 1979;Anderson et al, 2008;Schwander et al, 2010;Bopp et al, 2014;Klein et al, 2016). However, caste development is more frequently mediated by environmental factors, whereas sex development is more frequently mediated by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…temperature and nutrition) or genetic (e.g. sex chromosomes and genetic caste determination) factors leading to development of alternative phenotypic states (Brian, 1979;Anderson et al, 2008;Schwander et al, 2010;Bopp et al, 2014;Klein et al, 2016). However, caste development is more frequently mediated by environmental factors, whereas sex development is more frequently mediated by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ants of the genus Cardiocondyla are exceptional in their extent of realized phenotypic plasticity. Therefore, they provide a promising model for dissecting molecular and genomic differences underlying the evolution of novel developmental switches through genetic accommodation, both within and between closely related species (Klein et al, ; Schrader et al, ; Schrader, Helanterä, & Oettler, ). Our study is only the first step towards uncovering these molecular differences.…”
Section: Discussionmentioning
confidence: 99%
“…At the developmental and genetic level, Klein et al () showed that wing polyphenism in males and females in C. obscurior evolved through co‐option of ancestral sex‐differentiation pathways (including the terminal sex differentiation transcription factor doublesex ), which is known to control a large suite of developmental toolkit genes. Furthermore, an initial RNAseq study on early third instar larvae of C. obscurior showed a large morph‐specific gene expression bias, and in particular, that wingless male at this stage are characterized by an enriched expression of genes associated with larval and imaginal disc development (Schrader et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Neither brother-sister mating nor mother-son mating lead to the production of diploid males [57,58], suggesting that Cardiocondyla has evolved an alternative to sl-CSD. A recent study documented sex-specific splicing of transformer, a key player in insect sex determination, but it is still unclear what initially triggers the development of males from unfertilized eggs and females from fertilized eggs [59]. In C. obscurior, experimental siblingmating over 10 generations resulted in fitness decreases, such as shortened queen lifespan, higher brood mortality and more strongly male-biased sex ratios [57].…”
Section: (A) Queen Number and Morphologymentioning
confidence: 99%